MYOCARDIAL PERFORMANCE INDEX IN PATIENTS OF SICKLE CELL DISORDER - chaturvedi, Anuj; kumar, Sunil; Chaturvedi, Sourav; ANDHALE, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Sickle cell disorder is a group of diseases where shape of erythrocytes changes to sickle shape and the fragility of cell membrane increases due to deoxygenation. It is caused by a point mutation at sixth position in beta globin chain, where valine is replaced by glutamic acid. Sickle cell cardiomyopathy includes 4-chamber dilation and in some patient’s myocardial fibrosis, diastolic dysfunction, abnormal perfusion reserve and very rarely myocardial iron overload maybe present. Myocardial performance index (MPI) is a numeric value which is obtained by measuring cardiac time interval, obtained by a Doppler echocardiogram that expresses systolic and diastolic function both, and is used to investigate right and left ventricular function. Due to the geometric shape of right ventricle, its function is crucial to analyse using non-invasive methods, so it may be a specifically useful index. On extensive search, no such study has been done in India till now, that’s why we have decided to undertake this study as MPI may be a useful non-invasive and sensitive tool for assessing the subclinical cardiac LV and RV dysfunction in patients with sickle cell disorder. - To compare the myocardial performance index in sickle cell patients and age and sex matched healthy controls. To compare the myocardial performance index in sickle cell crisis v/s stable sickle cell disease patients. Prospective cross sectional study with control group was carried out at AVBRH , a tertiary care teaching hospital situated in the rural area of Wardha District. Patients ≥ 18 years of age with diagnosed/newly detected cases of sickle cell anaemia admitted in Medicine Department and those attending medicine OPD both males and females were included. Normal healthy males and females with age and sex match were taken as controls. Out of 61 cases 22.95% of patients had MPI ≤0.40 and 77.5% had MPI >0.40 whereas in control group 93.85% had MPI ≤0.40 and 6.15% had MPI >0.40. Out of 10 patients with sickle cell crisis 30% had MPI ≤0.40 and 70% had MPI >0.40 and amongst stable sickle cell disease patients 13.73% had MPI ≤0.40 and 86.27% had MPI >0.40. This Doppler echocardiographic study will be helpful to identify early abnormalities in systolic and diastolic function in Sickle cell disorder more commonly in sickle cell crisis patients.